Perspectives on managing man-environment relationship - Chakraborty, Satyesh C. (1983)
This paper attempts to focus on the need for proper understanding of the relationship between man and environment in the context of environment management. Man-environment relationship has now become a paradox and this really is man's own creation. Landscape approach provides a better basis for understanding man-environment relationship. Therefore concepts of physical landscape, cultural landscape, ecology and ecosystem should become the integral part of the education for environment management.